2018
DOI: 10.1016/j.aju.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic subinguinal varicocelectomy in 100 consecutive cases: Spermatic cord vascular anatomy, recurrence and hydrocele outcome analysis

Abstract: ObjectiveTo evaluate the detailed vascular anatomy of the spermatic cord during subinguinal microscopic varicocelectomy and to assess the outcome of the cases with regard to varicocele recurrence and hydrocele formation.Patients and methodsIn all, 100 varicocele cases including 74 left-sided and 26 bilateral, comprising 126 spermatic cord units with clinically palpable varicoceles underwent microscopic subinguinal varicocelectomy. Detailed description of vascular anatomy of the spermatic cords was reported. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…In recent years, studies showed that robot-assisted microscopic varicocelectomy is as successful as the conventional methods (27). However, microscopic subinguinal varicocelectomy is the golden standard for the treatment of varicocele (28,29). This method includes the treatment of venous system by preserving testicular arterial and lymphatic vessels.…”
Section: P-values For the Correlation Analysis Between Semen Analysis Results And Spermatic Vein Diameters Measured By Cdus In Group 2 Anmentioning
confidence: 99%
“…In recent years, studies showed that robot-assisted microscopic varicocelectomy is as successful as the conventional methods (27). However, microscopic subinguinal varicocelectomy is the golden standard for the treatment of varicocele (28,29). This method includes the treatment of venous system by preserving testicular arterial and lymphatic vessels.…”
Section: P-values For the Correlation Analysis Between Semen Analysis Results And Spermatic Vein Diameters Measured By Cdus In Group 2 Anmentioning
confidence: 99%
“…Chan, Wright, and Goldstein (2005) reported an accidental artery ligation rate of 0.9%, and testicular atrophy was developed in 5% of these patients. Intraoperative Doppler utrasound was applied in some institutions to facilitate the detection of arteries (Al-Kandari et al, 2018;Almekaty et al, 2019;Guo et al, 2017). Under Doppler ultrasonography, these arteries were characterised by high-pitched pulsatile flow sound.…”
Section: Discussionmentioning
confidence: 99%
“…Many surgical approaches have been adopted in varicocele repair, such as macroscopic retroperitoneal, laparoscopic transperitoneal, microscopic subinguinal and percutaneous embolisation. The ideal solution should be characterised by occluding all the spermatic veins while preserving arteries and lymphatics (Al-Kandari et al, 2018). Although the best option is still under debate, microscopic varicocelectomy shows tremendous promise in treatment of varicocele with great efficacy and minimised complications and recurrence (Ding et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, a meta-analysis of the comparative efficacy of various treatment techniques for varicocele revealed that subinguinal varicocelectomy was associated with a very low odds of recurrence (OR = 0.05; 95% CI: 0.01–0.19) in comparison to retroperitoneal open surgery. 22 In 2018, Alkandari et al 23 investigated the recurrence of varicocele in 100 patients (74 unilateral and 26 bilateral cases) who underwent microscopic subinguinal varicocelectomy, with a mean follow-up period of 6 months. The recurrence was reported in 3 out of the 126 (2.3%) spermatic cord units investigated, going in line with our observation.…”
Section: Discussionmentioning
confidence: 99%